2016
DOI: 10.1089/dna.2016.3226
|View full text |Cite
|
Sign up to set email alerts
|

SPRY4 Intronic Transcript 1 Promotes Epithelial–Mesenchymal Transition Through Association with Snail1 in Osteosarcoma

Abstract: Osteosarcoma is an aggressive tumor and the most common malignancy of the skeleton. Due to pulmonary metastasis, the 5-year survival rate is still unsatisfactory. It has been reported that SPRY4 intronic transcript 1 (SPRY4-IT1) promotes cell growth, invasion, and inhibits apoptosis in several cancers. However, the role of SPRY4-IT1 in osteosarcoma remains unclear. In the present study, we investigated the role of SPRY4-IT1 in osteosarcoma cells. Loss- and gain-of-function assays demonstrated that SPRY4-IT1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Besides these two mechanisms, others have also been identified, including the direct interaction of lncRNAs with proteins involved in EMT [243,250,264] and regulation of mRNA translation [154]. For many of the lncRNAs identified so far, exactly how they regulate EMT is unknown (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these two mechanisms, others have also been identified, including the direct interaction of lncRNAs with proteins involved in EMT [243,250,264] and regulation of mRNA translation [154]. For many of the lncRNAs identified so far, exactly how they regulate EMT is unknown (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of this complexity include SPRY4-IT1, which is derived from an intron of SPRY4, is upregulated in many cancers and has been shown to induce EMT in colorectal cancer, gliomas, HCC, oesophageal squamous cell carcinoma and osteosarcoma [264,266,267,380,381,382,383,384]. In bladder cancer, SPRY4-IT1 is upregulated [385] and induces metastasis whereby it acts as a ceRNA for miR-101-3p, resulting in up-regulation of EZH2 [265].…”
Section: Lncrnas and Emt: The Main Playersmentioning
confidence: 99%
“…In addition, SPRY4-IT1 also demonstrated the oncogenic role via targeting zinc finger protein 703 in breast cancer and ESCC [15, 20]. In the osteosarcoma, SPRY4-IT1 can promote epithelial mesenchymal transition via interaction with Snail [21]. More importantly, the knock-down of SPRY4-IT1 inhibited cell growth and cell differentiation, also induced apoptosis in melanoma [10].…”
Section: Discussionmentioning
confidence: 99%
“…We then determined whether SPRY4-IT1 expression influences tumor-like characteristics such as proliferation and apoptosis [24]. Our results showed that knockdown of SPRY4-IT1 by siRNA in LoVo and SW480 cells was shown to significantly inhibit CRC cell growth and colony formation, and increase cell apoptosis, whereas the ectopic expression of SPRY4-IT1 significantly enhances cell proliferation in RKO cell lines.…”
Section: Discussionmentioning
confidence: 99%